Toripalimab-Induced Dermatomyositis in a Patient with Metastatic Melanoma - Jingrong Lin; Minmin Xue; Mingyang Gao; Pu Yu; Shixin Han (Adis, Springer Healthcare, 2020)
Abstract Toripalimab is a monoclonal antibody targeting programmed cell death protein 1 (PD-1). It has recently been approved as an immune checkpoint inhibitor in second-line therapies in patients with unresectable or metastatic melanoma; however, it may be associated with various immune-related adverse events (irAEs). Here we report a case of toripalimab-induced dermatomyositis in a patient receiving treatment for metastatic melanoma. The symptoms were relieved by discontinuing toripalimab and administering once-daily intravenous methylprednisolone 1 mg/kg. We suggest that this case serves a warning to clinicians of the need to be aware of the possiblilty of toripalimab-induced dermatomyositis. Early recognition and treatment may prevent progression and improve prognosis of this irAE.